Catedral - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Catedral nuestra señora de las nieves construida entre 1928 a 1931 yurimaguas
ENGLISH: Our Lady of the Snows Cathedral built between 1928 and 1931 yurimaguas

SPANISH: Catedral nuestra señora de las nieves construida entre 1928 a 1931 yurimaguas
ENGLISH: Our Lady of the Snows Cathedral built between 1928 and 1931 yurimaguas
Cathedral
Keywords: Cathedral--Yurimaguas (Peru)|~|Catedral|~|Yurimaguas (Perú)